2013
DOI: 10.1371/journal.pone.0052094
|View full text |Cite|
|
Sign up to set email alerts
|

A Ham1p-Dependent Mechanism and Modulation of the Pyrimidine Biosynthetic Pathway Can Both Confer Resistance to 5-Fluorouracil in Yeast

Abstract: 5-Fluorouracil (5-FU) is an anticancer drug and pyrimidine analogue. A problem in 5-FU therapy is acquired resistance to the drug. To find out more about the mechanisms of resistance, we screened a plasmid library in yeast for genes that confer 5-FU resistance when overexpressed. We cloned five genes: CPA1, CPA2, HMS1, HAM1 and YJL055W. CPA1 and CPA2 encode a carbamoyl phosphate synthase involved in arginine biosynthesis and HMS1 a helix-loop-helix transcription factor. Our results suggest that CPA1, CPA2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 39 publications
(40 reference statements)
5
28
0
Order By: Relevance
“…Carlsson et al () have previously shown that overexpression of the Ham1 gene in yeast protects against the exogenous supply of the non‐canonical, mutagenic pyrimidine nucleoside 5‐fluorouracil (5‐FU). The yeast Ham1 gene can protect against several non‐canonical nucleosides, including 6‐ N ‐hydroxylaminopurine (Kozmin et al , ; Noskov et al , ), 5‐fluorocytosine, and 6‐azauracil (Carlsson et al , ). To investigate whether U/CBSV Ham1 proteins can also provide protection from 5‐FU, resistance assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Carlsson et al () have previously shown that overexpression of the Ham1 gene in yeast protects against the exogenous supply of the non‐canonical, mutagenic pyrimidine nucleoside 5‐fluorouracil (5‐FU). The yeast Ham1 gene can protect against several non‐canonical nucleosides, including 6‐ N ‐hydroxylaminopurine (Kozmin et al , ; Noskov et al , ), 5‐fluorocytosine, and 6‐azauracil (Carlsson et al , ). To investigate whether U/CBSV Ham1 proteins can also provide protection from 5‐FU, resistance assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…The open reading frame in each deletion strain has been replaced by the KanMX selection cassette [ 29 ]. The plasmids pCPA1, pCPA2, pHMS1, pYJL055w, pHAM1 have been described previously [ 16 ]. Plasmid pYJL055w is referred to as pLOG1 in the present paper in order to make the genetic nomenclature consistent.…”
Section: Methodsmentioning
confidence: 99%
“…We previously carried out a screen in yeast for genes that confer resistance to 5-FU when overexpressed from a high copy number plasmid [ 16 ]. Among the cloned resistance genes we found HAM1 , which encodes inosine triphosphate pyrophosphatase, an enzyme that dephosphorylates non-canonical purine nucleoside triphosphates ITP, dITP and XTP and thus prevents their incorporation into DNA and RNA [ 17 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S . cerevisiae , Ura2 is bifunctional carbamoylphosphate synthetase/aspartate transcarbamylase and catalyzes the first two enzymatic steps in the de novo biosynthesis of pyrimidines [ 51 , 52 ], while it is not verified by direct assays and still uncharacterized in C . albicans .…”
Section: Discussionmentioning
confidence: 99%